2022
DOI: 10.1177/20552173211069852
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of dimethyl fumarate versus fingolimod in a cohort of patients with multiple sclerosis using standardized, quantitative outcome metrics

Abstract: Background Prior studies suggest comparable effectiveness of dimethyl fumarate (DMF) and fingolimod (FTY) in multiple sclerosis (MS) using relapse, Expanded Disability Status Score (EDSS), and magnetic resonance imaging (MRI) lesion metrics. Objective Compare the real-world effectiveness of DMF versus FTY using quantitative, validated neuroperformance tests, MRI, and serum neurofilament light chain (sNfL) outcomes while controlling for between-group differences. Methods Patients were eligible if on DMF or FTY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Some of them were conducted solely in a single centre [30,[39][40][41][42][43], some of them were posthoc analyses of the pivotal studies [44][45][46], some used a relatively small cohort [30,39,40,43,47,48]. Meanwhile, others have focused only on a single objective [49][50]; except a few studies [51,52], the follow-up period was surprisingly brief [43,[53][54][55] in several reports. Furthermore, some studies employed patients with both progressive and relapsing-remitting disease type [37].…”
Section: Discussionmentioning
confidence: 99%
“…Some of them were conducted solely in a single centre [30,[39][40][41][42][43], some of them were posthoc analyses of the pivotal studies [44][45][46], some used a relatively small cohort [30,39,40,43,47,48]. Meanwhile, others have focused only on a single objective [49][50]; except a few studies [51,52], the follow-up period was surprisingly brief [43,[53][54][55] in several reports. Furthermore, some studies employed patients with both progressive and relapsing-remitting disease type [37].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies reported a better performance of S1P modulators compared to an injectable DMT (two studies with IFN; one with GA; and one with both IFN and GA) [39,43,46,50]. Other DMTs were used as comparisons such as Natalizumab (NTZ) (three studies) [41,47,56], Alemtuzumab (ATZ) (one study) [56], DMF (two studies) [56,57], and TFL (two studies) [45,56]. In these studies, no significant differences were found with these DMTs, with the exception of the study by Glasmacher et al [56] where TFL and DMF were associated with significant worsening over time in cognitive assessment scores compared to FTY and CLAD.…”
Section: Sphingosinte-1-phosphate Modulatorsmentioning
confidence: 99%
“…Only two studies include data on neurofilaments (sNFL) [54,57]. In one of these studies, higher levels of sNFLs correlated with greater CI and BVL, and patients treated with S1P modulators had a significant reduction in sNFL levels compared to placebo [54].…”
Section: Sphingosinte-1-phosphate Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eligibility criteria were as follows: patients enrolled in the Multiple Sclerosis Partners Advancing Technology and Health Solutions network and had follow-ups in the network for more than one year. In the overall cohort, there was no significant difference noted in the neuro performance or MRI outcomes, including the brain volume loss between DMF (702 patients) and FTY (600 patients) groups [ 22 ].…”
Section: Reviewmentioning
confidence: 99%